1991
DOI: 10.1161/01.cir.83.6.1995
|View full text |Cite
|
Sign up to set email alerts
|

Association of human leukocyte class II antigens with rheumatic fever or rheumatic heart disease in a Brazilian population.

Abstract: BACKGROUND The incidence of rheumatic heart disease is great in Brazil. We analyzed the distribution of human leukocyte (HLA) antigens in a Brazilian population sample with rheumatic fever or rheumatic heart disease, with the aim of better understanding the mechanisms involved. METHODS AND RESULTS HLA class I (A, B, and C) and class II (DR and DQ) antigen distribution was studied in 40 patients with diagnosis of rheumatic fever or rheumatic heart diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
14

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 21 publications
6
60
1
14
Order By: Relevance
“…Romatizmal karditli hastaların romatizmal ateşin diğer klinik bulgularını taşıyanlardan ayrı olarak incelendiği veya çoğunluğunu mitral kapak hastalığının oluşturduğu romatizmal kalp hastalığının tek başına incelendiği çalış-malarda nispeten benzer HLA ilişkileri saptandığını göz-lenmektedir. 4,11,20,[24][25][26] Stanevicha ve ark 10 yaptıkları çalışmada mitral yetersizliği olan hastalarda HLA-DRB1*07 ve DQB1*0401-2'yi multivalvüler lezyonu olanlarda HLA-DRB1*07 ve DQB1*0302'yi yüksek sıklıkta saptadıklarını bildirmektedir. Guedez ve ark 15 RKH hastalarını birden fazla kapak hastalıklı hastalar ve mitral kapak hastalığı olan (MY veya MY+mitral darlığı) olarak sınıflayıp kontrollerle karşılaş-tırmışlardır.…”
Section: Discussionunclassified
“…Romatizmal karditli hastaların romatizmal ateşin diğer klinik bulgularını taşıyanlardan ayrı olarak incelendiği veya çoğunluğunu mitral kapak hastalığının oluşturduğu romatizmal kalp hastalığının tek başına incelendiği çalış-malarda nispeten benzer HLA ilişkileri saptandığını göz-lenmektedir. 4,11,20,[24][25][26] Stanevicha ve ark 10 yaptıkları çalışmada mitral yetersizliği olan hastalarda HLA-DRB1*07 ve DQB1*0401-2'yi multivalvüler lezyonu olanlarda HLA-DRB1*07 ve DQB1*0302'yi yüksek sıklıkta saptadıklarını bildirmektedir. Guedez ve ark 15 RKH hastalarını birden fazla kapak hastalıklı hastalar ve mitral kapak hastalığı olan (MY veya MY+mitral darlığı) olarak sınıflayıp kontrollerle karşılaş-tırmışlardır.…”
Section: Discussionunclassified
“…Several different HLA alleles, in particular HLA-DR7, have been associated with RHD and the development of valvular lesions. [10][11][12][13][14] By furthering the recognition of streptococcal peptides through the HLA system, the presence of these alleles likely enhances autoimmune inflammatory processes and amplifies disease severity.…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…T-cell clones from heart lesions of RHD patients have shown the ability to simultaneously recognize heart tissue-derived proteins and streptococcal M5 protein peptides, 36 in particular, immunodominant peptide residues 81-96 and 83-103, 10,37 epitopes also recognized by peripheral T lymphocytes in the context of HLA-DR7. 38 Furthermore, analysis of the N-terminal portion of the M5 protein and cardiac myosin has yielded three distinct cardiac myosin epitopes targeted by molecular mimicry in the S2 and light meromyosin regions.…”
Section: Molecular Mimicrymentioning
confidence: 99%
“…This is based on evidence of a familial association (4), controlled studies (5,6) and the fact that only 2-3% of individuals exposed to rheumatogenic group A streptococcal pharyngitis go on to develop ARF (1). Several studies have suggested that genetic predisposition to ARF is linked to human leukocyte antigen (HLA) class 2 alleles (7,8). However, there has been controversy concerning the nature of the susceptibility or protective alleles (9).…”
Section: Introductionmentioning
confidence: 99%